Lost in the sun - Graff, Lisa (Lisa Colleen), 1981- (New York, NY : Philomel Books, an imprint of Penguin Group (USA), 2015)
"As Trent Zimmerman struggles to move past a traumatic event that took place several months earlier, he befriends class outcast Fallon Little, who helps him understand that he can move on"--
Reading Counts!
Keywords: Friendship -- Fiction; Guilt -- Fiction; Brothers -- Fiction; Disfigured persons -- Fiction; Remarriage -- Fiction; Tricks -- Fiction; Friendship -- Juvenile fiction; Guilt -- Juvenile fiction; Brothers -- Juvenile fiction; Disfigured persons -- Juvenile fiction; Remarriage -- Juvenile fiction